MANAGING INTERPERSONAL MEANING IN SOCIAL MEDIA: A CASE STUDY OF INDONESIAN LANGUAGE USE - Putu Nur Ayomi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2021)
Social media has become an important platform for everyone to broadcast information, opinions, and emotion freely and borderless in today's society. Among other social media, Twitter is the most well-known social media platform for idea-sharing. With a resource such as hashtags, people can search, follow, and contribute to a specific topic, which can create a nationwide and even worldwide discussion. With such a high engagement between users, how the twitter users use language to manage interpersonal role-relationship effectively will determine how smooth a communication goes. Character education is an integral part of Indonesia's education system.  Therefore, in this internet era, it is also essential to understand the language resources of interpersonal meaning that students can exploit to engage more positively while exercising their freedom of expression in social media. This study draws upon the Systemic Functional Linguistic's (SFL) theory of interpersonal metafunction (Halliday, 1978; Halliday & Matthiessen, 2014; Martin, 1992) that focuses on Mood and Modality and  the Appraisal system (Martin, J.R.; White, 2005). As a case study, the data are taken from a trending topic in Indonesia Twitter, by choosing purposively some data that can best reflect the variety of interpersonal meaning. This study shows that specific interpersonal language resources can produce a more negotiated stance and solidarity that can lessen personal conflicts between users and encourage more positive communication.